The adaptation strategy of PT Charoen Pokphand Indonesia (Food Division) in facing the dynamics of the processed chicken industry - Paramitha, Dyah Ayu; Jahroh, Siti; Asnawi, Yudha Heryawan (Indonesian Journal of Multidisciplinary Science, 2024)
This study aims to identify the current business model of PT Charoen Pokphand Indonesia (Food Division), analyze internal and external business environmental factors affecting it, and design a new business model to adapt to the competition in the processed chicken industry in Indonesia. This study uses nonprobability sampling method with purposive sampling technique to select respondents, selected based on special expertise and knowledge in the field studied. This research uses data processing and analysis techniques involving mapping the company's business model into 9 elements of the business model canvas (BMC) and formulate adaptation strategies and develop new business models with a blue ocean strategy perspective through a framework of four actions: elimination, subtraction, improvement, and addition. The SWOT analysis revealed that CP FOOD's strengths lie in its value proposition, while weaknesses are in its marketing activities. The research will provide input and advice for future strategies and serve as a reference for academics to develop strategies for increasing competitiveness in the processing chicken industry.